Brand Storytelling dan Purchase Decision Sepatu Olahraga yang Dimediasi Customer Brand Engagement di Bandung Raya - Eka Septiarini (Universitas Pendidikan Indonesia, 2023)
Many companies have implemented social media in terms of product promotion. Ease and efficiency are the fundamental reasons why social media, such as Instagram and TikTok, are the main platforms for product marketing. One way to promote using social media is to make a brand storytelling video to introduce the product offered, in this case, sports shoes. This study aimed to determine the relationship between customer brand engagement and purchasing decisions for sports shoes, especially in Greater Bandung. The method used in this study is descriptive and associative, in which the survey is distributed to respondents who live in Greater Bandung. The analysis results using descriptive and associative quantitative methods show that two independent variables, namely Brand Storytelling (BS) and Customer Brand Engagement (CBE), significantly influence purchasing decisions (PD) for sports shoe products, both directly and when consumer brand engagement acts as a mediator on purchase decision.